Influence of pilates method training on the balance of the elderly: a systematic review - Filho, Edson Meneses Silva; Albuquerque, Jéssica Andrade de (Manual Therapy, Posturology & Rehabilitation Journal, 2016)
Introduction: Getting older is a process characterized by physical changes, which include, among other, the loss of reproductive function and the decline of motor function and it is sometimes associated with chronic diseases. The aging process induces a natural functional decline, and considering this phenomenon, it is primordial research studies that indicate interventions that promote improvements in the health status of the elderly. Objective: To analyse, through a sistemic review, the effects of the pilates method on the static and dinamic balance in the elderly. Method: This systematic review followed the recommendations of the Preferred Reporting Itens for Systematic Reviews and Meta-Analyses (PRISMA) and the searches were carried out in database: IBECS, PubMed, LILACS, EMBASE, SCIELO e PEDro from descriptors “pilates, exercício físico e idosos”, and their names in english and spanish. Results: There were analysed 11 original articles about the theme and most of them showed positive results of the pilates method on the static and dinamic balance in the elderly. Conclusion: The pilates method showed significant results on the static and dinamic balance in the elderly, but there should be better quality studies to guarantee its effectiveness.